Advances in hospitality and leisure. Vol. 4 - Chen, Joseph S. (Emerald, 2008)
Advances in Hospitality and Leisure, a peer-reviewed series, delivers refreshing insights from a host of scientific studies in the domains of hospitality, leisure, and tourism. It provides a platform to galvanize thoughts on contemporary issues and emerging trends essential to theory advancement, as well as professional practices from a global perspective. The main focus of this series is to transcend the innovative methods of inquiry so as to inspire new research topics that are vital and have been in large neglected. The series is keen to address the needs of the populace having interests in disseminating ideas, concepts and theories derived from scholarly investigations. Potential readers may retrieve useful texts to outline new research agendas, suggest viable topics for a dissertation work, and augment the knowledge of the subjects of interest.
Includes index.
Keywords: Hospitality industry.; Tourism.; elektronické knihy; electronic books